Emerging insights on functions of the anthelmintic flubendazole as a repurposed anticancer agent. (1st December 2021) - Khachigian, Levon M.
Abstract: While flubendazole has been used as a macrofilaricide in humans and animals for some 40 years, work in vitro and in preclinical models over the last decade has suggested its potential use as an anticancer agent. This article reviews recent studies in a range of tumor types indicating novel functions for flubendazole in its control of processes associated with tumor growth, spread and renewal including ferroptosis, autophagy, cancer stem-like cell killing and suppression of intratumoral myeloid-derived suppressor cell accumulation and programmed cell death protein 1. Flubendazole's potential use in clinical oncology will require further understanding of its mechanistic roles, range of inhibition of cancer types, capacity for adjunctive therapy and possible reformulation for enhanced solubility, bioavailability and potency. Highlights: Flubendazole has been used as a macrofilaricide in humans and animals for 40 years but recent studies suggest its potential use as an anticancer agent. Flubendazole regulates tumor growth, spread and renewal. It inhibits tumor angiogenesis and can synergize with chemotherapeutic agents. Emerging evidence indicate that flubendazole has effects on ferroptosis, autophagy, cancer stem-like cells, intratumoral myeloid-derived suppressor cell accumulation and PD-1 levels. These properties suggest the utility of flubendazole and other benzimidazole derivatives as repurposed or derivatized cancer agents.